London's accessibility indicators: Strengths, weaknesses, challenges - Aliasgar Inayathusein; Simon Cooper (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
The paper provides an introduction to London's context and the need for accessibility indicators. It overviews existing indicators developed and used by Transport for London, including: PTAL, ATOS (Access to Services) and catchment-based measures, as well as giving an introduction to TfL's online web portal for connectivity assessment: WebCAT. There is also a review of calculation principles, a summary of user cases and an analysis of the strengths and weaknesses of each method. A second section describes indicators (e.g. PTAL incorporating cycling, and walking catchment analysis) that are currently under development as part of TfL's commitment towards prioritising healthy streets and sustainable modes of transport. The final section focuses on challenges and opportunities identified during the development of these indicators.
Keywords: 330